A high-adhesion wear-resistant ink composition, preparation method thereof and BOPP composite film

By using wear-resistant components of multi-branched cage-shaped silsesquioxane and ABA-type multi-branched chain segment structures in aqueous inks, the problem of insufficient adhesion and wear resistance of aqueous ink on BOPP films is solved, and an ink composition with high adhesion and wear resistance is achieved, meeting the needs of long-term transportation and storage.

CN118165571BActive Publication Date: 2025-04-25JIANGSU BRIGHT NEW MATERIAL CO LTD

Patent Information

Application Number
CN202410453979.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-16
Publication Date
2025-04-25
Estimated Expiration
2044-04-16

AI Technical Summary

Technical Problem

The existing water-based inks have insufficient adhesion and wear resistance on the BOPP film, making it difficult to meet the needs of long-term transportation and storage.

Method used

A high adhesion and wear-resistant ink composition is adopted, which includes aqueous polyurethane resin, aqueous acrylic resin, wear-resistant components, aqueous color paste and defoaming agent. By octachloropropyl cage-shaped silsesquioxane as an initiator, a multi-branched cage-shaped silsesquioxane is formed, nano-alumina and acrylamide are grafted to form ABA-type multi-branched chain segments to improve the adhesion and wear resistance of the ink.

Benefits of technology

It achieves high adhesion and wear resistance on the BOPP film, and can maintain the integrity and clarity of the ink during transportation and storage, meeting the needs of long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of ink, and specifically discloses a high-adhesion wear-resistant ink composition, a preparation method thereof, and a BOPP composite film. The composition comprises the following components in parts by weight: 20-35 parts of waterborne polyurethane resin; 15-25 parts of waterborne acrylic resin; 15-25 parts of wear-resistant components; 20-40 parts of waterborne color paste; 0.4-0.8 parts of defoamer; 5-10 parts of deionized water; the wear-resistant component uses octachloropropyl caged silsesquioxane as an initiator, and alternately initiates the polymerization of alkenyl silane coupling agent-modified nano-alumina and acrylamide to obtain multi-branched caged silsesquioxane; the branched chain is an ABA-type copolymer segment. The ink composition prepared in the present application has excellent adhesion and wear resistance, and a BOPP composite film is prepared by multi-layer composite. The BOPP composite film of the present application has excellent wear resistance and long service life, and is suitable for industrial storage and transportation packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ink compositions, and more specifically, to a high-adhesion and wear-resistant ink composition, a preparation method thereof, and a BOPP composite film. Background Art

[0002] Biaxially oriented polypropylene film (BOPP) is an important packaging material with excellent physical stability, mechanical strength, air tightness and transparency. When BOPP film is used in the packaging field, it is often necessary to spray printing ink on its surface, such as coding, marking, etc. for identification and classification. However, the surface of BOPP film is non-polar, with low surface free energy, poor printing effect, poor adhesion of ink on the film surface, and easy to collide and fade during transportation, which cannot meet the requirements of transportation, storage, and long-term clarity. Treating the surface of BOPP film is a common way to improve surface wettability, such as corona treatment and plasma treatment. Corona treatment has a certain effective time limit and high process requirements. Plasma treatment does not improve wettability to meet the requirements of long-term use. In addition, the existing wear-resistant inks cannot take into account the high wear resistance and high adhesion performance on BOPP.

[0003] Environmentally friendly water-based ink has always been a popular development direction. It does not add organic solvents, avoiding environmental pollution and affecting human health. However, the adhesion of water-based ink on the substrate is also poor, and the mechanical properties of water-based ink are not as good as oil-based ink, and the wear resistance is poor. The compounding of different resins can improve the ink performance to a certain extent. For example, polyurethane resin has excellent mechanical properties, cold resistance, and wear resistance, and acrylic resin has excellent water resistance and weather resistance. The mixed use of the two resins can improve the overall performance of water-based ink to a certain extent, but it cannot meet the requirements of high adhesion and high wear resistance on BOPP film.

[0004] In the existing method of improving water-based ink, wear resistance is often improved by adding wear-resistant agents such as fillers with wear-resistant properties, but the addition of wear-resistant agents has a certain impact on adhesion, and wear-resistant agents have poor dispersibility and instability in water-based systems, affecting the quality of ink. Based on this, how to develop a water-based ink that has excellent adhesion and wear resistance on BOPP film and can meet the needs of long-term transportation and storage is a problem that needs to be solved. Summary of the invention

[0005] In order to solve the problem of having both high adhesion and wear resistance of water-based ink on BOPP film, the present application provides a high-adhesion and wear-resistant ink composition, a preparation method thereof and a BOPP composite film.

[0006] First, the present application provides a high-adhesion wear-resistant ink composition, comprising the following components in parts by weight: 20-35 parts of waterborne polyurethane resin; 15-25 parts of waterborne acrylic resin; 15-25 parts of wear-resistant component; 20-40 parts of waterborne color paste; 0.4-0.8 parts of defoamer; 5-10 parts of deionized water; the wear-resistant component uses octachloropropyl caged silsesquioxane as an initiator, alternately initiating the polymerization of alkenyl silane coupling agent-modified nano-alumina and acrylamide to obtain multi-branched caged silsesquioxane; the branch is an ABA type copolymer segment. Preferably, 28 parts of waterborne polyurethane resin; 20 parts of waterborne acrylic resin; 20 parts of wear-resistant component; 30 parts of waterborne color paste; 0.6 parts of defoamer; 8 parts of deionized water.

[0007] Polyurethane resin has excellent mechanical properties, cold resistance, and wear resistance, and acrylic resin has excellent water resistance and weather resistance. Mixing them can improve the comprehensive performance of ink. The inventor selects the wear-resistant component based on the wear resistance and adhesion of the ink. The wear-resistant component of the present application is a multi-branched polymer. Octachloropropyl caged silsesquioxane is used as the initial initiator of free radical active polymerization to initiate monomers, and polymer segments are grafted thereon in dynamic equilibrium polymerization. The formed polymer is still terminated with a carbon-chlorine bond and can be used as a macromolecular active initiator to continue to initiate polymerization. In addition, octachloropropyl caged silsesquioxane has eight active initiation endpoints, which can initiate active polymers to form multi-branched polymer structures. In the present application, octachloropropyl caged silsesquioxane is used as an initiator to initiate the polymerization of carbon-carbon double bonds in nano-alumina modified with an alkenyl silane coupling agent, so that wear-resistant nano-alumina particles are grafted into the chain segment, and the obtained macromolecule is then used as an initiator to initiate the polymerization of acrylamide. Further, the polymerization product is used as an initiator to initiate the nano-alumina modified with an alkenyl silane coupling agent, thereby forming a three-segment ABA type (nano-alumina grafted chain segment-acrylamide chain segment-nano-alumina grafted chain segment) multi-branched chain segment.

[0008] The wear-resistant filler nano-alumina itself has excellent wear resistance, and adding it to ink can improve the wear resistance of the ink. However, it is easy to agglomerate and settle in the aqueous system, which not only affects the wear resistance but also the adhesion of the ink. The present application grafts it into the multi-branched segment. On the one hand, the nano-alumina relies on the multi-branched structure to form a sufficient dispersion and the nano-alumina exists stably, and is not easy to agglomerate and settle. On the other hand, due to reasonable dispersion, better wear resistance can be achieved when the amount of nano-alumina added is very small, thereby reducing the input of nano-alumina and improving the adhesion of the ink.

[0009] The inventors found that the wear-resistant component formed by using acrylamide monomer to polymerize the B segment has a better contribution to the wear resistance and adhesion performance of the ink. This may be because the polyacrylamide segment improves the hydrophilicity of the component on the one hand, and based on the ABA-type structural effect, further improves the dispersion of nano-alumina, thereby improving the wear resistance. On the other hand, it contains amino groups and carboxyl groups in water-based acrylic resins that can be bonded, and has similar amide bonds with water-based polyurethane resins, which improves the molecular force, thereby achieving better cross-linking and compatibility between resins, thereby improving the adhesion of the ink, making the wear-resistant filler more stable in the formed cross-linked structure, and the nano-alumina has good dispersibility and high stability in the resin, and even does not require the addition of additional dispersants, thereby improving the wear resistance.

[0010] The present invention selects octachloropropyl caged silsesquioxane as an initiator. On the one hand, octachloropropyl caged silsesquioxane itself has high wear resistance and can improve the adhesion and glossiness of the composition. On the other hand, the nano-alumina particles evenly distributed in the side chains work together to form an effective wear-resistant system, which greatly increases the wear resistance in the case of a small amount of wear-resistant particles. The inventor further found through experiments that the polymerization of three ABA-type (nano-alumina grafted chain segment-acrylamide chain segment-nano-alumina grafted chain segment) is better in wear resistance than the chain segment of AB-type structure, indicating that compared with AB-type side chains, ABA-type side chains and octachloropropyl caged silsesquioxane form a better wear-resistant dispersion system.

[0011] The preparation method of the wear-resistant component of the present application comprises the following steps: S1: mixing and polymerizing alkenyl silane coupling agent-modified nano-alumina, octachloropropyl caged silsesquioxane, a catalyst, a ligand, and a toluene solvent, and then post-treating to obtain component A; S2: mixing and polymerizing acrylamide, component A, a catalyst, a ligand, and a toluene solvent, and then post-treating to obtain component B; S3: mixing and polymerizing alkenyl silane coupling agent-modified nano-alumina, component B, a catalyst, a ligand, and a toluene solvent, and then post-treating to obtain the wear-resistant component.

[0012] The mass ratio of the alkenyl silane coupling agent modified nano alumina in S1, the acrylamide in S2, and the alkenyl silane coupling agent modified nano alumina in S3 is 1:(3-5):1.

[0013] Conventional atom transfer radical polymerization systems can be used for the preparation of the wear-resistant components of the present application, such as Cu-catalyzed ATRP, AGET ATRP, Fe-catalyzed ATRP, AGET ATRP, etc., and the present application prefers the Cu-catalyzed ATRP system.

[0014] Specifically, S1: adding 80-100 parts of alkenyl silane coupling agent modified nano-alumina to toluene, passing nitrogen to deoxygenate, adding 1-2 parts of octachloropropyl caged silsesquioxane, mixing and stirring, then adding 2-4 parts of catalyst and 4-8 parts of ligand, heating to 80-100°C for polymerization for 6-8 hours, dissolving the polymer in tetrahydrofuran, precipitating with a large amount of methanol, filtering and drying to obtain component A; S2: adding 200-600 parts of acrylamide to toluene, passing nitrogen to deoxygenate, adding 15-25 parts of component A and catalyst, S3: dissolve 80-100 parts of alkenyl silane coupling agent modified nano alumina in toluene, deoxygenate with nitrogen, add 30-50 parts of B component, 2-4 parts of catalyst and 4-8 parts of ligand, heat to 100-120°C and polymerize for 6-8 hours, dissolve the product in tetrahydrofuran, precipitate with a large amount of methanol, filter and dry to obtain component B. The catalytic system in the present application can select any conventional catalytic system that can be used to catalyze ATRP. Furthermore, the catalyst is preferably cuprous chloride, and the ligand is preferably tri[2-(dimethylamino)ethyl]amine, which has a tetradentate structure. Compared with pentamethyl divinyl triamine, it has good coordination and high activity for the polymerization of the modified silane coupling agent and acrylamide of the present application initiated by octachloropropyl caged silsesquioxane as an initiator, and compared with bipyridine and cyclic amines, its linear structure is more suitable for the initiator system of the present application.

[0015] Through the process design, it was found that when the mass ratio of the alkenyl silane coupling agent modified nano alumina in S1, the acrylamide in S2, and the alkenyl silane coupling agent modified nano alumina in S3 was 1:(3-5):1, better wear resistance was achieved and the adhesion was also maintained at a good level. The inventors believe that this may be because when the amount of acrylamide is lower than the above range, the wear-resistant component is not hydrophilic enough, the bonding effect with the water-based acrylic resin and the water-based polyurethane resin is small, and the dispersibility of the nano-alumina is insufficient, resulting in a decrease in wear resistance and adhesion. When the amount of acrylamide is higher than the above range, on the one hand, the content of nano-alumina is relatively reduced, and a fully dispersed wear-resistant system is not formed, which affects the wear resistance. On the other hand, too many acrylamide bonds are not conducive to the mechanical properties of the ink, and the reduction of methacryloyloxy groups in the system affects the compatibility effect in the composite resin, which is not conducive to the improvement of adhesion. Therefore, the increase in the content of excessive acrylamide has limited effect on the improvement of adhesion. The polymer monomer ratio within the above range can make the wear-resistant component have good compatibility in the system of polyurethane and acrylic resin compound, good cross-linking, and sufficient dispersion of the wear-resistant component, thereby having good wear resistance and adhesion.

[0016] Preferably, the preparation method of the alkenylsilane coupling agent modified nano-alumina comprises: dissolving the alkenylsilane coupling agent in an ethanol aqueous solution, adding the nano-alumina, heating for reaction, filtering, washing, and drying.

[0017] More preferably, the alkenyl silane coupling agent includes one or both of KH570 and A-171.

[0018] The silane modification of nano-alumina adopts a conventional hydrolysis method. Specifically, 20-30 parts of silane coupling agent are added to 100 parts of 30% by mass ethanol aqueous solution, and then 10-20 parts of nano-alumina are added, heated to 90-110°C for reflux reaction for 1-2 hours, and then filtered, washed, and dried to obtain modified nano-alumina. All silane coupling agents containing carbon-carbon double bonds can be used to prepare modified nano-alumina. KH570 and A-171 are preferred in this application, and KH570 is more preferred. KH570 has a structure similar to acrylic resin after polymerization, and has better compatibility in the ink components of this application.

[0019] Preferably, the acid value of the water-based acrylic resin of the present application is 40-80 mg KOH / g. Within the above range, the ink has good mechanical properties, adhesion, wear resistance and spraying effect. If the acid value is too low, the bonding effect between the acrylamide segment and the acrylic resin in the wear-resistant component is reduced, resulting in unsatisfactory adhesion and poor wear resistance, while if the acid value is too high, it is easy to cause poor fluidity, resulting in poor spraying effect and poor water resistance of the ink.

[0020] The water-based color paste of the present application can be blue color paste, red color paste, phthalocyanine green color paste, black color paste, etc., which can be selected according to the coloring requirements. Conventional commercial brands or preparation methods can be used to obtain the water-based color paste of the present application. The defoamer is preferably a water-based defoamer; such as TEGO FOAMEX 805. In other embodiments, the ink of the present application can also include auxiliary agents such as a drying agent and a dispersant.

[0021] Secondly, the present application provides a method for preparing a high-adhesion and wear-resistant ink composition, comprising the following steps: weighing components according to the ratio, mixing and stirring the wear-resistant component, aqueous polyurethane resin, and aqueous acrylic resin, then adding aqueous color paste, defoaming agent, and deionized water to mix, and filtering the material to obtain the ink composition.

[0022] The wear-resistant component, water-based polyurethane resin and water-based acrylic resin are mixed in advance to improve the compatibility of the ink components, which is beneficial to improving performance.

[0023] On the other hand, the present application provides a BOPP composite film, which is obtained by printing the above-mentioned high adhesion and wear-resistant ink composition on the entire or partial area of ​​the surface of the BOPP base film.

[0024] Preferably, the base film can be plasma pretreated before the ink composition is printed. The plasma-treated base film increases the surface wettability and forms active groups such as hydroxyl and carboxyl groups on the surface. The wear-resistant component in the ink of the present application has excellent water solubility, and the amino group can react with the surface active group of the base film to enhance the adhesion of the ink, so that the BOPP film has strong adhesion and wear resistance when used for packaging and transportation, and the integrity of the printed ink is maintained for a long time.

[0025] In another embodiment of the present application, a wear-resistant primer can be applied to all or part of the base film before the ink composition is printed to form a composite film structure of base film / primer / ink, which can be used to improve the overall wear resistance of the BOPP film. The wear-resistant primer can preferably include the following components: 20-35 parts of waterborne polyurethane resin; 15-25 parts of waterborne acrylic resin; 25-35 parts of wear-resistant components; 10-20 parts of pigments; 10-20 parts of fillers; 0.4-0.8 parts of defoamers; 0.5-2 parts of dispersants; 5-10 parts of deionized water; wherein the waterborne polyurethane resin, waterborne acrylic resin, wear-resistant components, and defoamers can be the same or different from those in the ink composition, preferably the same components as the ink, to improve the compatibility of the ink and the primer, so that the adhesion of the primer and the ink is better, and the ink can be permanently attached to the surface of the packaging film. The filler can be selected from one or more of talcum powder, calcium carbonate, and barium sulfate; the pigment can be selected from one or more of titanium dioxide and red iron oxide. Compared with ink, when the content of wear-resistant component as primer is increased, the adhesion of ink can be improved. The increase in the content of wear-resistant component provides more acrylamide segments on the one hand. When applied to the plasma-treated base film, it can react with the active groups on the surface of the BOPP film after plasma treatment. On the other hand, it may also react with the active groups in the ink, thereby increasing the adhesion of the ink to the BOPP film. Therefore, for the composite film used in the present application, the content of wear-resistant component in the primer is higher than that in the ink, preferably 25-35 parts of wear-resistant component.

[0026] In summary, this application has at least the following beneficial effects:

[0027] The present application prepares a wear-resistant component and adds it to ink to form a wear-resistant ink. The wear-resistant component uses octachloropropyl caged silsesquioxane as an initiator to initiate the polymerization of carbon-carbon double bonds in nano-alumina modified with alkenyl silane coupling agent, so that wear-resistant nano-alumina particles are grafted in the chain segment, and then the obtained macromolecular initiator is used to initiate the polymerization of acrylamide, and further, the nano-alumina modified with alkenyl silane coupling agent is initiated, thereby forming a three-segment ABA type (nano-alumina grafted chain segment-acrylamide chain segment-nano-alumina grafted chain segment) multi-branched chain segment. Nano-alumina relies on the multi-branched structure to form a sufficient dispersion, so that nano-alumina exists stably and is not easy to agglomerate and settle. When the amount of nano-alumina added is very small, better wear-resistant effect can be achieved, which reduces the input amount of nano-alumina and improves the adhesion of the ink. The use of acrylamide monomer to polymerize the B segment has a better contribution to the wear resistance and adhesion performance of the ink. This may be because, on the one hand, the polyacrylamide segment improves the hydrophilicity of the component, and based on the ABA-type structural effect, further promotes the dispersion of nano-alumina, thereby improving wear resistance. On the other hand, it contains amino groups and carboxyl groups in water-based acrylic resins that can achieve cross-linking, and has similar amide bonds to water-based polyurethane resins, which improves molecular forces, thereby achieving better cross-linking and compatibility between resins, thereby improving adhesion, making the wear-resistant filler more stable in the formed cross-linked structure, and improving wear resistance. Octachloropropyl caged silsesquioxane itself has high wear resistance, which can improve the adhesion and gloss of the composition. Through the uniformly distributed nano-alumina particles in the side chains, they work together to form an effective wear-resistant system, which increases wear resistance with a small amount of wear-resistant particles.

[0028] Among the wear-resistant components, the polymerization of three ABA-type (nano-alumina grafted segment-acrylamide segment-nano-alumina grafted segment) has better wear resistance than the AB-type structured segment, indicating that the ABA-type branched chain and octachloropropyl caged silsesquioxane work together to form a better wear-resistant dispersion system.

[0029] 3. The present application obtains better wear resistance and maintains a good adhesion level by controlling the mass ratio of the alkenylsilane coupling agent modified nano-alumina in S1, the acrylamide in S2, and the alkenylsilane coupling agent modified nano-alumina in S3 to 1:(3-5):1. When the amount of acrylamide is lower than the above range, the wear-resistant component is not hydrophilic enough, the bonding with the water-based acrylic resin and the water-based polyurethane resin is reduced, and the dispersibility of the nano-alumina is insufficient, resulting in a decrease in wear resistance and adhesion. When the amount of acrylamide is higher than the above range, on the one hand, the content of nano-alumina is relatively reduced, and the dispersion of the wear-resistant component in the system is uneven. On the other hand, too many acrylamide bonds are not conducive to the mechanical properties of the ink, and have little effect on improving the adhesion of the ink.

[0030] 4. The present application preferably uses KH570 to modify the nano-alumina particles and use it in the ink system. It has better compatibility in the ink components of the present application and better ink adhesion.

[0031] 5. The present application improves the long-lasting adhesion of the ink on the BOPP film by plasma treatment of the BOPP film and combines it with the ink formula of the present application. The wear resistance of the BOPP film is improved by setting the primer component, and the adhesion between the ink layer-primer and the primer-base film is improved, thereby achieving better adhesion of the ink on the film. DETAILED DESCRIPTION

[0032] The present application is further described in detail below in conjunction with the examples. The waterborne polyurethane resin used in the examples and preparation examples is selected from ADM-F206 of Shandong Aodemei Polymer Materials Co., Ltd.; the waterborne acrylic resin is selected from K-224 of Huizhou Qisheng Technology Co., Ltd., with an acid value of 50 mg KOH / g; octachloropropyl caged silsesquioxane (chloropropyl POSS) is purchased from Zhengzhou Alpha Chemical Co., Ltd.; the defoamer is selected from TEGO FOAMEX 805; the average particle size of nano-alumina is 30 nm. The waterborne color paste is selected from BASF waterborne color paste 8730. Other experimental reagents in the preparation examples or examples, unless otherwise specified, are conventional commercial brands or obtained through conventional preparation processes.

[0033] Preparation of wear-resistant components:

[0034] Preparation Example 1:

[0035] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0036] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of ligand tri[2-(dimethylamino)ethyl]amine and heat to 90°C for polymerization for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0037] S2: Add 160 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of cuprous chloride as catalyst, and 6 g of tris[2-(dimethylamino)ethyl]amine as ligand, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0038] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0039] Preparation Example 2:

[0040] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0041] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of ligand tri[2-(dimethylamino)ethyl]amine and heat to 90°C for polymerization for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0042] S2: Add 240 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of cuprous chloride as catalyst, 6 g of tris[2-(dimethylamino)ethyl]amine as ligand, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0043] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0044] Preparation Example 3:

[0045] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0046] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of ligand tri[2-(dimethylamino)ethyl]amine and heat to 90°C for polymerization for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0047] S2: Add 320 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of cuprous chloride as catalyst, and 6 g of tris[2-(dimethylamino)ethyl]amine as ligand, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0048] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0049] Preparation Example 4:

[0050] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0051] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of ligand tri[2-(dimethylamino)ethyl]amine and heat to 90°C for polymerization for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0052] S2: Add 400 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of catalyst cuprous chloride, 6 g of ligand tris[2-(dimethylamino)ethyl]amine, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0053] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0054] Preparation Example 5:

[0055] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0056] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of ligand tri[2-(dimethylamino)ethyl]amine and heat to 90°C for polymerization for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0057] S2: Add 480 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of cuprous chloride as catalyst, 6 g of tris[2-(dimethylamino)ethyl]amine as ligand, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0058] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0059] Preparation Example 6:

[0060] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0061] S1: Take 320g of the modified nano-alumina prepared in the above manner and add it to 900mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 9g of cuprous chloride catalyst and 18g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 90°C and polymerize for 21 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0062] Preparation Example 7:

[0063] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0064] S1: 160 g of the modified nano-alumina prepared in the above manner was added to 600 mL of toluene, and nitrogen was passed to deoxygenate. 1 g of octachloropropyl caged silsesquioxane was added and mixed and stirred. Then 6 g of cuprous chloride catalyst and 12 g of tri[2-(dimethylamino)ethyl]amine ligand were added, and the temperature was raised to 90° C. for polymerization for 14 hours. The polymer was dissolved in 10 mL of tetrahydrofuran, and a large amount of methanol was precipitated. After filtration, it was dried at 60° C. to obtain component A;

[0065] S2: Add 160 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component A of S1, 3 g of catalyst cuprous chloride, and 6 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0066] Preparation Example 8:

[0067] Add 320 g of acrylamide to 900 mL of toluene, pass nitrogen to deoxygenate, add 1 g of octachloropropyl caged silsesquioxane and mix, then add 9 g of cuprous chloride catalyst and 18 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 90° C. and polymerize for 21 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60° C. to obtain a wear-resistant component.

[0068] Preparation Example 9:

[0069] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0070] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of ligand tri[2-(dimethylamino)ethyl]amine and heat to 90°C for polymerization for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0071] S2: Add 160 g of methyl methacrylate to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of cuprous chloride as catalyst, and 6 g of tris[2-(dimethylamino)ethyl]amine as ligand, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0072] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0073] Preparation Example 10:

[0074] S0: Add 25g of silane coupling agent A-171 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0075] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of ligand tri[2-(dimethylamino)ethyl]amine and heat to 90°C for polymerization for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0076] S2: Add 160 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of cuprous chloride as catalyst, and 6 g of tris[2-(dimethylamino)ethyl]amine as ligand, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0077] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand tri[2-(dimethylamino)ethyl]amine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0078] Preparation Example 11:

[0079] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0080] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of pentamethyldivinyltriamine ligand and heat to 90°C for polymerization for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0081] S2: Add 160 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of catalyst cuprous chloride, and 6 g of ligand pentamethyldiethylenetriamine, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0082] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand pentamethyldiethylenetriamine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0083] Preparation Example 12:

[0084] S0: Add 25g of silane coupling agent KH570 to 100g of 30% by mass ethanol aqueous solution, then add 15g of nano-alumina and stir, heat to 100°C and reflux for 2h, filter, wash with water, and dry at 60°C to obtain modified nano-alumina.

[0085] S1: Take 80g of the modified nano-alumina prepared in the above manner and add it to 300mL of toluene, pass nitrogen to deoxygenate, add 1g of octachloropropyl caged silsesquioxane and mix and stir, then add 3g of cuprous chloride catalyst and 6g of bipyridine ligand, heat to 90°C and polymerize for 7 hours, dissolve the polymer in 10mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component A;

[0086] S2: Add 160 g of acrylamide to 300 mL of toluene, pass nitrogen to deoxygenate, add 20 g of component A, 3 g of cuprous chloride catalyst, and 6 g of bipyridine ligand, heat to 90°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain component B;

[0087] S3: Dissolve 80 g of modified nano-alumina in S0 in 300 mL of toluene, pass nitrogen to deoxygenate, add 40 g of component B, 3 g of catalyst cuprous chloride, and 6 g of ligand bipyridine, heat to 110°C and polymerize for 7 hours, dissolve the product in 10 mL of tetrahydrofuran, precipitate with a large amount of methanol, filter and dry at 60°C to obtain a wear-resistant component.

[0088] The conversion rate in the catalytic step of different ligands was calculated, conversion rate = product / (polymerization monomer + initiator)*100%, the results are as follows:

[0089] Table 1: Conversion rates of different ligand systems

[0090]

[0091] Combining Preparation Examples 1, 11, 12 and Table 1, it can be seen that by selecting three different ligands to catalyze the polymerization of the same monomer, the copper catalytic system formed by tri[2-(dimethylamino)ethyl]amine as a ligand exhibits better catalytic efficiency for the two different monomers of the present application. Example 1

[0092] 200 g of the wear-resistant component of Preparation Example 1, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition. Example 2

[0093] 200 g of the wear-resistant component of Preparation Example 1, 250 g of aqueous polyurethane resin, and 230 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition. Example 3

[0094] 200 g of the wear-resistant component of Preparation Example 1, 300 g of aqueous polyurethane resin, and 180 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition. Example 4

[0095] 200 g of the wear-resistant component of Preparation Example 2, 280 g of waterborne polyurethane resin, and 200 g of waterborne acrylic resin were mixed and stirred for 30 min, and then 300 g of waterborne color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition. Example 5

[0096] 200 g of the wear-resistant component of Preparation Example 3, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition. Example 6

[0097] 200 g of the wear-resistant component of Preparation Example 4, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition. Example 7

[0098] 200 g of the wear-resistant component of Preparation Example 5, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition. Example 8

[0099] 200 g of the wear-resistant component of Preparation Example 10, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition.

[0100] Comparative Example 1

[0101] 280 g of waterborne polyurethane resin and 200 g of waterborne acrylic resin were mixed and stirred for 30 min, and then 300 g of waterborne color paste, 6 g of defoaming agent and 280 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition.

[0102] Comparative Example 2

[0103] 200 g of the wear-resistant component of Preparation Example 6, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition.

[0104] Comparative Example 3

[0105] 200 g of the wear-resistant component of Preparation Example 7, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition.

[0106] Comparative Example 4

[0107] 200 g of the wear-resistant component of Preparation Example 8, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition.

[0108] Comparative Example 5

[0109] 200 g of the wear-resistant component of Preparation Example 9, 280 g of aqueous polyurethane resin, and 200 g of aqueous acrylic resin were mixed and stirred for 30 min, and then 300 g of aqueous color paste, 6 g of defoaming agent, and 80 g of deionized water were added and mixed and stirred for 30 min. The material was filtered to obtain an ink composition.

[0110] Performance testing:

[0111] 1. Adhesion fastness test: The ink compositions of the examples and comparative examples were coated on a BOPP film and cured according to the standard, and their adhesion fastness on the BOPP film was tested with reference to GB / T 13217.7-2009.

[0112] 2. Abrasion resistance test: The ink compositions of the examples and comparative examples were coated on a BOPP film and cured. The number of times the rubber wheel rotated when the substrate was exposed was observed using an RCA abrasion tester under a load of 175 g.

[0113] The performance test results of the embodiments and comparative examples are shown in Table 2:

[0114] Adhesion fastness / (%) Wear resistance / (times) Example 1 94 720 Example 2 95 731 Example 3 93 708 Example 4 97 763 Example 5 99 796 Example 6 99 751 Example 7 99 702 Example 8 92 710 Comparative Example 1 84 438 Comparative Example 2 79 654 Comparative Example 3 91 665 Comparative Example 4 99 497 Comparative Example 5 87 682

[0115] Combining Example 1 of the present application with Comparative Examples 1-5, it can be seen that the present application achieves excellent wear resistance and adhesion of the ink composition by adding the wear-resistant component, and the ABA-type branched multi-segment wear-resistant component has better adhesion and wear resistance than the A-type, AB-type, and B-type, reflecting the excellent ink adhesion and wear resistance of the ABA-type branched wear-resistant component. In addition, compared with methyl methacrylate, the wear-resistant component prepared by selecting acrylamide for copolymerization reflects more excellent ink adhesion and wear resistance.

[0116] It can be seen from Example 1 and Examples 4-7 that by adjusting the amount of monomer added during the polymerization process in the wear-resistant component branch chain, when the mass ratio of the alkenyl silane coupling agent modified nano alumina in S1, the acrylamide in S2, and the alkenyl silane coupling agent modified nano alumina in S3 is 1:(3-5):1 during the preparation process, the ink composition has excellent wear resistance and adhesion, among which 1:4:1 has the best effect. This may be because within this range, the components with acrylamide content in the ink have good crosslinking and compatibility, and the nano alumina is evenly dispersed and stably present in the resin system. The content of nano alumina is appropriate and can form a good wear-resistant system with octachloropropyl caged silsesquioxane, resulting in its adhesion and wear resistance being able to achieve an ideal level and meet the use requirements.

[0117] It can be seen from Example 1 and Example 8 that KH570 has better adhesion and wear resistance than A-171, indicating that the selection of coupling agent can improve the adhesion and wear resistance of ink to a certain extent.

[0118] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-adhesion and wear-resistant ink composition, characterized in that: The composition comprises the following components in parts by weight: 20-35 parts of waterborne polyurethane resin; 15-25 parts of water-based acrylic resin; 15-25 parts of wear-resistant components; 20-40 parts of water-based color paste; Defoaming agent 0.4-0.8 parts; 5-10 parts of deionized water; The wear-resistant component uses octachloropropyl caged silsesquioxane as an initiator to alternately initiate the polymerization of alkenyl silane coupling agent-modified nano-alumina and acrylamide to obtain multi-branched caged silsesquioxane; the branches are ABA-type copolymer segments; The preparation method of the wear-resistant component comprises: S1: Alkenyl silane coupling agent modified nano-alumina, octachloropropyl caged silsesquioxane, catalyst, ligand, toluene solvent are mixed and polymerized, and then post-treated to obtain component A; S2: mixing acrylamide, component A, catalyst, ligand, and toluene solvent, polymerizing, and post-treating to obtain component B; S3: The alkenyl silane coupling agent-modified nano-alumina, component B, catalyst, ligand, and toluene solvent are mixed and polymerized, and then post-processed to obtain a wear-resistant component.

2. The high adhesion and wear-resistant ink composition according to claim 1, characterized in that: The mass ratio of the alkenyl silane coupling agent modified nano alumina in S1, the acrylamide in S2, and the alkenyl silane coupling agent modified nano alumina in S3 is 1:(3-5):

1.

3. The high adhesion and wear-resistant ink composition according to claim 1, characterized in that: The method for preparing alkenyl silane coupling agent modified nano alumina comprises: adding alkenyl silane coupling agent into ethanol aqueous solution, then adding nano alumina, heating reaction, filtering, washing and drying.

4. The high adhesion and wear-resistant ink composition according to claim 1, characterized in that: The alkenyl silane coupling agent includes one or two of KH570 and A-171.

5. The high adhesion and wear-resistant ink composition according to claim 1, characterized in that: The acid value of the water-based acrylic resin is 40-80 mg KOH / g.

6. A method for preparing a high-adhesion and wear-resistant ink composition according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: weighing components according to a proportion, mixing and stirring a wear-resistant component, a water-based polyurethane resin and a water-based acrylic resin, adding a water-based color paste, a defoamer and deionized water, and filtering the material to obtain an ink composition.

7. A BOPP composite film, characterized in that: The high-adhesion and wear-resistant ink composition according to any one of claims 1 to 5 is printed on the entire or partial area of ​​the surface of the BOPP base film to obtain a composite film.

8. The BOPP composite film according to claim 7, characterized in that: The base film is plasma pre-treated before printing the ink composition.

9. The BOPP composite film according to claim 8, characterized in that: Before printing the ink composition, a wear-resistant primer is applied to all or part of the base film; the wear-resistant primer comprises the following components in parts by weight: 20-35 parts of waterborne polyurethane resin; 15-25 parts of water-based acrylic resin; 25-35 parts of wear-resistant components; Pigment 10-20 parts; Filler 10-20 parts Defoaming agent 0.4-0.8 parts; Dispersant 0.5-2 parts; 5-10 parts of deionized water; The wear-resistant component uses octachloropropyl caged silsesquioxane as an initiator to alternately initiate the polymerization of alkenyl silane coupling agent-modified nano-alumina and acrylamide to obtain multi-branched caged silsesquioxane; the branches are ABA-type copolymer segments; The preparation method of the wear-resistant component comprises: S1: Alkenyl silane coupling agent modified nano-alumina, octachloropropyl caged silsesquioxane, catalyst, ligand, toluene solvent are mixed and polymerized, and then post-treated to obtain component A; S2: mixing acrylamide, component A, catalyst, ligand, and toluene solvent, polymerizing, and post-treating to obtain component B; S3: The alkenyl silane coupling agent-modified nano-alumina, component B, catalyst, ligand, and toluene solvent are mixed and polymerized, and then post-processed to obtain a wear-resistant component.

Citation Information

Patent Citations

  • Preparation method for acrylamide graft modification nanometer aluminum oxide epoxy composite insulating material

    CN104693685A

  • Flame-retardant acrylic fabric and preparation method thereof

    CN114960185A

Cited By

  • Water-based wear-resistant ink and preparation method thereof

    CN120966308A